Establishing the availability of the recently erected binomen Phyllotis pehuenche (Rodentia, Cricetidae, Sigmodontinae) - Jayat, Jorge Pablo (2022)
In 2021, Jayat et al. propose a new species of sigmodontine rodent, named Phyllotis pehuenche, for the populations of the P. xanthopygus species complex from southwestern Mendoza and western Neuquén provinces, Argentina. The formal description of the species, published in a modifiable electronic supplementary material, do not fulfill the requirements established by the Amendment on e-publication (ICZN 2012) of The Fourth Edition of the International Code of Zoological Nomenclature (ICZN 1999), rendering the name Phyllotis pehuenche unavailable. The objective of this note was to comply with the provisions of the code and make the name available. Here we offer a summarized version of the original description of this species. In this note, we provide a taxonomic account for P. pehuenche, including its synonymy, type locality, holotype and paratypes, providing the etymology of the specific epithet, and offering a diagnosis for the species and comments regarding its geographic distribution. With the provided information, we comply with the provisions of The International Code of Zoological Nomenclature (ICZN 1999, 2012) making the name available.